Formulasi Gel Hand Sanitizer Ekstrak Buah Belimbing Wuluh dengan Variasi Karbopol 940 dan HPMC - Ferdy Firmansyah; Hastri Kholifah; Lutfi Chabib (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The hand hygiene is compulsory to keep maintain. It is one of the important things to prevent the diseases that caused by microorganisms infection or the other infectious diseases, especially during this COVID-19 pandemic. Most of the hand sanitizer (HS) products are used alcohol as an antibacterial. The right way to reduce the use of HS-containing alcohol is by replacing them with using the active substances derived from herbal plant extracts, one of it is the star fruit (BBW). Flavonoid is one of the component in BBW. Thus, the purpose of this study is to determine the effect of a good combination of Carbopol 940 base and HPMC on the physical properties of HS BBW gel preparations. The formulation of hand sanitizer gel was used a combination of Carbopol 940 and HPMC with the variation concentrations of 0.5%; 0.75%; 1% and 0.25%; 0.5%; 0.75%. Evaluation of the physical properties of the gel preparation was determined based on the observations of consistency, scent, colour, pH, homogeneity, dispersibility, and physical stability using the freeze and thaw method for 6 storage cycles at 4°C and 45°C. The results shown that the variations concentration of gelling agents affect pH and dispersion. The higher the concentration of the gelling agent, the lower pH value and dispersion. This can be seen in each formula in the first week with pH 6.31, 6.13, and 5.62, and spreadability of 6.2, 5.8, and 5.6. Tests on the fourth week in a row with pH of 5.53, 5.49, and 5.23 and a spread of 5.2, 5.0, and 4.5. Variations in the concentration of HPMC and Carbopol was not affected to the organoleptic, homogeneity, and also the stability.